2019
DOI: 10.14740/gr1204
|View full text |Cite
|
Sign up to set email alerts
|

Kratom-Induced Cholestatic Liver Injury Mimicking Anti-Mitochondrial Antibody-Negative Primary Biliary Cholangitis: A Case Report and Review of Literature

Abstract: Kratom is an herbal supplement used to relieve chronic pain or opioid withdrawal symptoms. Recent news articles covering adverse effects associated with kratom use have brought attention to its organ toxicities. Reports of kratom-induced hepatic toxicity are limited and only three case reports of kratom-induced liver injury with histopathologic examination of the liver biopsies are available. A 40-year-old female presented with symptoms of mixed cholestatic and hepatocellular liver injury without clear etiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…The lymphocytic cholangitis, a typical feature of PBC and unusual medication-injury finding, raised initial concern for underlying early stage PBC. This is of lesser concern given her negative antinuclear antibody and AMA status, trend toward rapid resolution of liver enzymes, and a case report by Aldyab et al[ 10 ] in 2019 that reported a case of kratom toxicity with granulomatous cholangitis (another form of florid duct lesion) that mimicked PBC. This was from a 40-year-old female presenting with liver injury after Kratom use who initially perceived to have AMA-negative PBC but diagnosed with Kratom induced liver injury after rapid normalization of liver enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…The lymphocytic cholangitis, a typical feature of PBC and unusual medication-injury finding, raised initial concern for underlying early stage PBC. This is of lesser concern given her negative antinuclear antibody and AMA status, trend toward rapid resolution of liver enzymes, and a case report by Aldyab et al[ 10 ] in 2019 that reported a case of kratom toxicity with granulomatous cholangitis (another form of florid duct lesion) that mimicked PBC. This was from a 40-year-old female presenting with liver injury after Kratom use who initially perceived to have AMA-negative PBC but diagnosed with Kratom induced liver injury after rapid normalization of liver enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Kratom use has been often linked to liver toxicity. Kratom has been associated with biliary cholangitis and cholestasis in several cases (67,(103)(104)(105)(106)(107)(108)(109)(110) and with one case of hepatomegaly (111), but also with acute hepatitis (112). Mitragynine inhibits hepatic and intestinal cytochrome P450 3A activities (113) and hepatic microsomal CYP2D6 (114), thus increasing blood levels of other concomitantly administered drugs that are metabolized by these isoenzymes, that is, most psychiatric drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Regretfully, some otherwise promising and promotional HILI cases did not benefit from causality assessment by RUCAM (Table 5) as shown in reports originating from Argentina (114), Austria (115), Belgium (116), Canada (117,118), China (107,(119)(120)(121), France (121,122), Germany (118,(123)(124)(125)(126)(127)(128)(129)(130)(131), Italy (132,133). Japan (134), the Netherlands (135), New Zealand (136), South Africa (137), Thailand (138), and the US (139)(140)(141)(142)(143)(144)(145)(146)(147)(148)(149)(150)(151)(152)(153)(154). RUCAM could have provided substantial support for published conclusions and provided more power to HILI related issues.…”
Section: Published Hili Cases Lacking Causality Assessment By Rucammentioning
confidence: 99%